PUBLIC SECTOR ACCOUNTING CYCLE: PROCUREMENT OF GOODS/SERVICES IN THE GOODS/SERVICES PROCUREMENT WORK UNIT GARUT REGENCY - Nunik Lestari Dewi; Vinny Stephanie Hidayat; Nindy Tanison (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The goods/services procurement style is one of the public sector accounting cycles that requires transparency and accountability for more effective budget absorption. This procurement mechanism in the Garut Regional Government need to comply with Presidential Regulation Number 12 of 2021 concerning Government Goods and Services Procurement. Therefore, this research aims to analyze procurement cycle, optimal implementation, inhibiting factors, and auction failures of procurement of goods/services in Garut Regency. Data were collected from all employees of the Garut Regency Goods/Services Procurement Work Unit through observation, interviews and supporting documents. The results showed that implementation of goods/services procurement in 2023 at the UKPBJ (Goods/Services Procurement Work Unit) Garut Regency described the right procurement cycle in accordance with Presidential Regulation Number 12 of 2021. Procurement process is optimal and more efficient in terms of budget ceiling and estimated price. In conclusion, the inhibiting factors namely the ignorance of procurement actors, and inadequate functional resources led to the failure of six auction packages and inappropriate work quality.